Multilayer CPC composite material and preparation method thereof
By using atomic diffusion and rolling technology in the preparation of copper/molybdenum copper/copper composites, the existing process flow and poor binding force are solved, and efficient preparation of materials and comprehensive performance are achieved.
Patent Information
- Application Number
- CN202411581898.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The preparation process of existing copper/molybdenum copper/copper composite materials is cumbersome, and the interface bonding force of the board is poor, making it difficult to effectively improve the comprehensive performance of the material.
During the preparation of molybdenum copper material, the copper plate and the molybdenum copper plate are combined with the molybdenum copper plate, and the bonding force between the plates is further improved through rolling, simplifying the preparation process.
It improves the bonding strength between the plates, reduces the defects between the plate interfaces, and improves the overall performance of the material.
Smart Images

Figure CN119387595A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new material preparation, and in particular to a multilayer CPC composite material and a preparation method thereof. Background Art
[0002] CPC composite materials are also called copper / molybdenum copper / copper composite materials. With the continuous increase in microelectronic packaging density, packaging materials are required to have higher heat transfer performance. In addition, in order to reduce the thermal stress that causes the failure of ceramic substrates and solders, the thermal expansion coefficient of packaging materials should match that of ceramic and semiconductor materials as much as possible. In such market demand, copper / molybdenum copper / copper composite materials came into being.
[0003] There are many existing copper / molybdenum copper / copper material preparation processes, including rolling method, explosion method, hot pressing-rolling method and other processes. Among them, the rolling method is to connect the cleaned copper plate and the molybdenum copper plate by rivets, and then use a rolling mill to composite roll the plate to obtain the final product. The explosion method is to connect the cleaned copper plate and the molybdenum copper plate by explosion welding to obtain a composite material. The hot pressing-rolling method is to first weld the copper plate and the molybdenum copper plate together through a hot pressing process, and then improve the bonding strength of the copper plate and the molybdenum copper plate by rolling to obtain a copper / molybdenum copper / copper composite material with the required thickness. Regardless of the explosion method or the rolling method, the copper plate and the molybdenum copper plate need to be composited together first, and then the bonding strength of the copper plate and the molybdenum copper plate is improved by rolling to obtain a copper / molybdenum copper / copper composite material. The above-mentioned preparation processes all need to prepare the molybdenum copper material first, and then composite the molybdenum copper material and the copper plate. The preparation process is cumbersome, and the interface bonding strength of the plate is poor, and it is difficult to effectively improve the comprehensive performance of the overall material. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a multilayer CPC composite material and a preparation method thereof. In the process of preparing molybdenum-copper materials, the present invention combines copper plates and molybdenum-copper plates together through the effect of atomic diffusion, and further improves the bonding strength between the plates through rolling, thereby improving the bonding strength between the plates on the basis of reducing the process of the preparation process, reducing the defects between the interfaces of the plates, and helping to improve the comprehensive performance of the material.
[0005] A multi-layer CPC composite material and a preparation method thereof of the present invention are achieved by the following technical solutions:
[0006] The first object of the present invention is to provide a method for preparing a multilayer CPC composite material, comprising the following steps:
[0007] Step 1, preparing mixed powder:
[0008] Molybdenum powder, copper powder and a mixing aid are mixed and then dried to obtain a mixed powder.
[0009] It should be noted that, during the research process, the present invention found that if the molybdenum powder and the copper powder are directly mixed, there will be a problem of uneven powder mixing. Therefore, the present invention preferably performs powder mixing by adding a mixing aid on the basis of the molybdenum powder and the copper powder, so that the molybdenum powder and the copper powder can be fully mixed, so as to form a molybdenum-copper layer material with uniform composition in the subsequent process. The molybdenum powder and the copper powder are first mixed to form a mixed powder with uniform composition.
[0010] Step 2, compression treatment:
[0011] The mixed powder is pressed to obtain a blank.
[0012] It should be noted that, in the present invention, the mixed powder is first pressed into a blank by a pressing process, so as to make the molybdenum-copper layer material from the mixed powder.
[0013] Step 3, hot pressing semi-melt infiltration treatment:
[0014] The blank is placed between two copper plates to form a preform with a copper plate / blank / copper plate sandwich structure; the preform is subjected to a hot pressing semi-melt infiltration treatment to achieve a preliminary composite of the molybdenum-copper alloy layer and the copper plates on both sides to obtain a multilayer CPC precursor.
[0015] It should be noted that the present invention forms a preform of a copper plate / blank / copper plate sandwich structure by placing the blank between two copper plates, so as to facilitate the subsequent hot pressing semi-melt infiltration technology to process the preform. In the process of hot pressing semi-melt infiltration, the middle layer in the preform, that is, the copper powder in the blank, will be molten and fully wrapped around the molybdenum powder, thereby forming a molybdenum-copper alloy layer; at the same time, the copper plates on the upper and lower sides of the preform diffuse into the molybdenum-copper alloy layer formed in the middle layer through diffusion, so that the molybdenum-copper alloy layer and the copper plates on both sides are initially compounded while preparing the molybdenum-copper alloy layer, and a multi-layer CPC composite material with "copper layer, molybdenum-copper alloy layer and copper layer" is obtained, thereby simplifying the preparation process and saving preparation costs.
[0016] Step 4, post-processing:
[0017] The multi-layer CPC precursor is flattened, and then rolled and annealed in sequence to obtain the multi-layer CPC composite material.
[0018] It should be noted that the present invention uses flattening treatment to make the copper layer surfaces on both sides of the multi-layer CPC precursor smooth and defect-free, with a surface roughness of ≤0.5 μm. In the trimmed multi-layer CPC precursor, the thickness ratio of the copper layer, the molybdenum-copper alloy layer and the copper layer is 1.08-1.28:1:1.08-1.28.
[0019] The present invention performs rolling treatment on the trimmed multi-layer CPC precursor obtained above according to the actual required thickness, so as to enhance the bonding force between the interfaces of the multi-layer materials through the rolling treatment.
[0020] The present invention adopts a multi-stage heating and multi-stage pressure adjustment method to perform hot pressing semi-melt infiltration treatment, which can achieve the initial combination of the copper layer and the molybdenum copper layer. In some preferred embodiments of the present invention, please refer to Figure 1 The hot pressing semi-infiltration treatment is carried out by the following steps:
[0021] 1) After the temperature is raised to 400°C to 600°C and the working pressure is increased to 4MPa to 6MPa by increasing the pressure by 0.5MPa to 1.5MPa for every 100°C increase in temperature, the first stage of heat preservation treatment is performed to preheat the hot pressing mold under this condition to prevent the mold from cracking due to excessive temperature increase. In some more preferred embodiments of the present invention, the time of the first stage of heat preservation treatment is 10min to 15min to ensure that the hot pressing mold can be preheated by the first stage of heat preservation treatment. In some other more preferred embodiments of the present invention, the temperature is raised to 400°C to 600°C within 30min to 40min.
[0022] 2) After the temperature is raised to 600°C to 900°C and the working pressure is increased to 15MPa to 20MPa by increasing the pressure by 2.5MPa to 3.5MPa for every 100°C increase in temperature, a second stage of heat preservation treatment is performed so that under this condition, the copper plate can eliminate part of the processing stress and prepare for the subsequent semi-infiltration to prepare the CPC precursor. In some more preferred embodiments of the present invention, the time of the second stage of heat preservation treatment is 10min to 20min to achieve the purpose of eliminating the stress of the copper plate. In some other more preferred embodiments of the present invention, the temperature is raised to 600°C to 900°C within 30min to 40min.
[0023] 3) After the temperature is raised to 1020°C to 1080°C and the working pressure is increased to 20MPa to 30MPa by increasing the pressure by 2.5MPa to 3.5MPa for every 100°C increase in temperature, a third stage of heat preservation treatment is performed to soften the copper plate and discharge the gas inside the copper plate under this condition. In some more preferred embodiments of the present invention, the third stage of heat preservation treatment is performed for 10min to 15min to soften the copper plate and discharge the gas inside the copper plate. In some other more preferred embodiments of the present invention, the temperature is raised to 1020°C to 1080°C within 5min to 10min.
[0024] 4) Under the condition of maintaining the pressure at 20MPa to 30MPa, after heating to 1250℃ to 1380℃, the fourth stage of heat preservation treatment is carried out to allow the melt infiltration reaction to occur under this condition, so that the copper liquid can penetrate into the molybdenum copper plate, and form a copper layer on the surface of both sides of the molybdenum copper to obtain a CPC preform. In some more preferred embodiments of the present invention, the time of the fourth stage of heat preservation treatment is 10min to 30min, so that the copper liquid can penetrate into the molybdenum copper plate and the layers are fully combined. In some other more preferred embodiments of the present invention, the temperature is raised to 1250℃ to 1380℃ within 20min to 30min.
[0025] 5) Under the condition of maintaining the pressure at 20MPa to 30MPa, the temperature is lowered to <1000°C and the pressure is unloaded, and then cooled to room temperature to obtain a multilayer CPC precursor, so that the bonding stress of the CPC preform is eliminated under this condition to prevent the material from deforming. Among them, in some more preferred embodiments of the present invention, the temperature is first lowered to 1000°C within 15min to 20min and kept at 1000°C for 10min to 20min before the pressure is unloaded to eliminate the stress of the CPC preform material.
[0026] In some more preferred embodiments of the present invention, before performing the hot pressing semi-infiltration treatment, the blank is first placed between two copper plates in the mold cavity to form a preform of a copper plate / blank / copper plate sandwich structure; and the height of the mold used is ensured to be 1.5 to 1.8 times higher than the overall thickness of the material.
[0027] In some preferred embodiments of the present invention, the particle size of the molybdenum powder is 20 μm to 400 μm, and the particle size of the copper powder is 30 μm to 500 μm, so that the molybdenum powder and the copper powder can better form a molybdenum-copper alloy pressed body.
[0028] In some preferred embodiments of the present invention, the copper plate is made of cold-rolled plate, and its state meets the requirements of GB / T2040, so as to minimize impurities in the copper plate and avoid introducing more impurities in the subsequent copper infiltration process.
[0029] In some preferred embodiments of the present invention, the mass ratio of the molybdenum powder to the copper powder is 80-90:10-20, so that a molybdenum-copper matrix with certain porosity is formed during the pressing stage, so that the copper liquid formed by the copper plate in the subsequent hot pressing and infiltration process can penetrate into the molybdenum-copper alloy layer.
[0030] In some preferred embodiments of the present invention, the mixing auxiliary agent is ethanol, and the mass of the mixing auxiliary agent is 0.5% to 2% of the mass of the first mixed powder.
[0031] In some preferred embodiments of the present invention, when the powder mixing process is performed, the mixing time is 2h to 10h to achieve the purpose of uniform mixing. In some more preferred embodiments of the present invention, the drying temperature after the powder mixing process is 50°C to 70°C, the drying time is 2h to 8h, and the powder is turned over every 15min to 30min during the drying process to ensure that the mixing aid is removed by drying, thereby avoiding the influence of the mixing aid on the subsequent molybdenum-copper composite effect.
[0032] It should be noted that the present invention does not specifically limit the mass ratio of the copper plate, the blank and the copper plate in the sandwich structure of the preform, and the mass ratio between the three can be adjusted accordingly according to actual needs. For example, when it is necessary to design a molybdenum-copper alloy containing 30% copper by mass, first press to obtain a blank of a molybdenum-copper alloy containing 20% copper by mass, reserve 10% of pores by mass in the blank, and then allow the copper plate to form copper liquid during the hot pressing and infiltration process, which infiltrates into the molybdenum-copper alloy, and finally form a molybdenum-copper alloy containing 30% copper by mass. In other preferred embodiments of the present invention, in the sandwich structure of the preform, the mass ratio of the copper plate, the blank and the copper plate is 1.1-1.3:1:1.1-1.3.
[0033] In some preferred embodiments of the present invention, during the pressing process, the density of the blank is controlled at 7.8 g / cm 3 ~8.9g / cm 3 In order to obtain the corresponding molybdenum-copper alloy preform in the infiltration stage, the mass fraction of copper required for subsequent copper infiltration can be calculated.
[0034] In some more preferred embodiments of the present invention, the present invention is specifically subjected to a pressing process by the following steps:
[0035] According to the required size requirements, select a pressing mold of corresponding specifications; then, place the obtained mixed powder in the pressing mold, and then place it in the automatic press; adjust the powder filling height according to the required size requirements and pressing density requirements, select the working pressure of the press, and set the holding time to 1s to 10s to obtain a density of 7.8g / cm 3 ~8.9g / cm 3 of the billet.
[0036] In some preferred embodiments of the present invention, during the rolling process, the reduction amount of each rolling is 3% to 8% to prevent the material from cracking during the rolling stage.
[0037] In some more preferred embodiments of the present invention, the present invention specifically performs rolling treatment by the following steps:
[0038] Each time rolling, the trimmed multi-layer CPC precursor is first placed in a nitrogen-hydrogen mixed furnace for preheating to 350°C to 500°C. When the temperature reaches the set stability, it is kept warm for 10min to 30min; and the roller is preheated to 100°C to 200°C; then, the preheated multi-layer CPC precursor and roller are taken out, and the preheated multi-layer CPC precursor is placed in the preheated roller for rolling, and the reduction is guaranteed to be 3% to 8%. Repeat several times until the required thickness is reached.
[0039] In some preferred embodiments of the present invention, please refer to Figure 2 The annealing treatment temperature is 550°C to 800°C, and the annealing holding time is 2h to 8h, so as to eliminate the material stress in the rolling stage.
[0040] The present invention also provides a multi-layer CPC composite material prepared by the above preparation method.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention first mixes molybdenum powder and copper powder by mixing auxiliary agents to form a mixed powder with uniform components, and then presses the mixed powder into a blank, and then forms a preform of a copper plate / blank / copper plate sandwich structure by placing the blank between two copper plates, so as to facilitate the subsequent hot pressing semi-melt infiltration technology to treat the preform. In the process of hot pressing semi-melt infiltration, the middle layer in the preform, that is, the copper powder in the blank, will be molten and fully wrapped around the molybdenum powder, thereby forming a molybdenum-copper alloy layer; at the same time, the copper plates on the upper and lower sides of the preform diffuse through diffusion, so that the atoms in the copper plates diffuse into the molybdenum-copper alloy layer formed in the middle layer, so as to achieve the preliminary compounding of the molybdenum-copper alloy layer and the copper plates on both sides while preparing the molybdenum-copper alloy layer, and finally, the above-obtained trimmed multi-layer CPC precursor is rolled according to the actual required thickness, so as to enhance the bonding force between the interfaces of the multi-layer materials through rolling treatment, and obtain a multi-layer CPC composite material with "copper layer, molybdenum-copper alloy layer and copper layer", thereby simplifying the preparation process and saving the preparation cost.
[0043] In the process of preparing molybdenum-copper materials, the present invention combines the copper plate and the molybdenum-copper plate together through the effect of atomic diffusion, and further improves the bonding strength between the plates through rolling. On the basis of reducing the process of the preparation process, the bonding strength between the plates is improved, the defects between the interfaces of the plates are reduced, and the comprehensive performance of the material is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is the process curve of the hot pressing semi-infiltration treatment of the present invention; Figure 1Among them, the temperature range corresponding to A is 400-600°C, the temperature range corresponding to B is 600-900°C, the temperature range corresponding to C is 1020-1080°C, and the temperature range corresponding to D is 1250-1380°C; a corresponds to the heating time before the first stage of insulation treatment, and the time range corresponding to a is 30min-40min; b corresponds to the insulation time of the first stage of insulation treatment, and the time range corresponding to b is 10min-15min; c corresponds to the heating time before the second stage of insulation treatment, and the time range corresponding to c is 30min-40min; d corresponds to the insulation time of the second stage of insulation treatment, and the time range corresponding to d is 10min-20min; e corresponds to the heating time before the third stage insulation treatment, and the time range corresponding to e is 5min~10min; f corresponds to the insulation time of the third stage insulation treatment, and the time range corresponding to f is 10min~15min; g corresponds to the heating time before the fourth stage insulation treatment, and the time range corresponding to g is 20min~30min; h corresponds to the insulation time of the fourth stage insulation treatment, and the time range corresponding to h is 10min~30min; i corresponds to the cooling time to 1000℃, and the time range corresponding to i is 15min~20min; j corresponds to the insulation time at 1000℃, and the time range corresponding to j is 10min~20min.
[0045] Figure 2 This is the process curve of the annealing treatment of the present invention; in the figure, A is the temperature of the annealing treatment, and the corresponding temperature range is 550°C to 800°C; a is the holding time of the annealing treatment, and the corresponding time range is 2h to 8h. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0047] Example 1
[0048] This embodiment provides a multi-layer CPC composite material, which is prepared by the following steps:
[0049] Step 1, preparing mixed powder:
[0050] 1.1) Molybdenum powder and copper powder are mixed in a mass ratio of 85:15 to obtain molybdenum-copper powder.
[0051] 1.2) Add ethanol to the molybdenum-copper powder obtained in 1.1), and the amount of ethanol added is 1% of the total mass of the molybdenum-copper powder to obtain an ethanol mixture of molybdenum-copper powder.
[0052] 1.3) The ethanol mixture of molybdenum and copper powders obtained in 1.2) was mixed for 6 hours and then dried at 60° C. for 5 hours to obtain a mixed powder.
[0053] Step 2, compression treatment:
[0054] The mixed powder obtained in 1.3) was placed in a pressing mold, the powder filling height was adjusted to be lower than 0.5 mold depth, and then placed in an automatic press. The working pressure of the press was selected to be 200 tons, and the holding time was set to 5s to obtain a density of 8.0g / cm 3 of the billet.
[0055] Step 3, hot pressing semi-melt infiltration treatment:
[0056] 3.1) The copper plate, the blank and the copper plate are placed in the mold cavity in sequence according to a mass ratio of 1.2:1:1.2, so that the blank is placed between the two copper plates to form a preform of a copper plate / blank / copper plate sandwich structure.
[0057] 3.2) Raise the temperature to 500°C within 35 minutes by increasing the pressure by 1 MPa for every 100°C rise in temperature. At the same time, increase the working pressure to 5 MPa and keep it at this temperature for 12 minutes.
[0058] 3.3) Raise the temperature to 750°C within 35 minutes by increasing the pressure by 3 MPa for every 100°C increase in temperature. At the same time, increase the working pressure to 17 MPa and keep it at this temperature for 15 minutes.
[0059] 3.4) Raise the temperature to 1060°C within 8 minutes by increasing the pressure by 3 MPa for every 100°C increase in temperature. At the same time, increase the working pressure to 25 MPa and keep it at this temperature for 12 minutes.
[0060] 3.5) While maintaining the pressure at 25 MPa, raise the temperature to 1300°C within 25 minutes and keep it at this temperature for 20 minutes.
[0061] 3.6) While maintaining the pressure at 25 MPa, the temperature was first lowered to 1000°C within 17 min and kept at 1000°C for 17 min, then the pressure was unloaded and then cooled to room temperature to obtain a multilayer CPC precursor.
[0062] Step 4, post-processing:
[0063] 4.1) Finishing treatment:
[0064] The multilayer CPC precursor obtained in 3.6) is trimmed by machining to make the copper layers on both sides smooth and defect-free with a surface roughness of 0.5 μm. In the trimmed multilayer CPC precursor, the thickness ratio of the copper layer, the molybdenum-copper alloy layer and the copper layer is 1.18:1:1.18.
[0065] 4.2) Rolling treatment:
[0066] Each time rolling, the trimmed multi-layer CPC precursor is first placed in a nitrogen-hydrogen mixed furnace for preheating to 400°C. When the temperature reaches the set stable temperature, it is kept warm for 20 minutes; and the roller is preheated to 150°C; then, the preheated multi-layer CPC precursor and roller are taken out, and the preheated multi-layer CPC precursor is placed in the preheated roller for rolling, and the reduction is guaranteed to be 5%. Repeat several times until the required thickness is reached.
[0067] 4.3) Annealing treatment:
[0068] The material after the rolling treatment in 4.2) is placed in a vacuum annealing furnace, heated to 650° C., and kept warm for 5 hours to obtain the multi-layer CPC composite material.
[0069] Example 2
[0070] This embodiment provides a multi-layer CPC composite material, which is prepared by the following steps:
[0071] Step 1, preparing mixed powder:
[0072] 1.1) Molybdenum powder and copper powder are mixed in a mass ratio of 80:20 to obtain molybdenum-copper powder.
[0073] 1.2) Add ethanol to the molybdenum-copper powder obtained in 1.1), and the amount of ethanol added is 0.5% of the total mass of the molybdenum-copper powder to obtain an ethanol mixture of molybdenum-copper powder.
[0074] 1.3) The ethanol mixture of molybdenum and copper powders obtained in 1.2) was mixed for 2 hours and then dried at 50° C. for 8 hours to obtain a mixed powder.
[0075] Step 2, compression treatment:
[0076] The mixed powder obtained in 1.3) is placed in a pressing mold, and the powder filling height is adjusted to be lower than half of the mold depth. Then, the mixture is placed in an automatic press, and the working pressure of the press is selected to be 200 tons, and the holding time is set to 10 seconds to obtain a density of 7.8 g / cm 3 of the billet.
[0077] Step 3, hot pressing semi-melt infiltration treatment:
[0078] 3.1) The copper plate, the blank and the copper plate are placed in the mold cavity in sequence according to a mass ratio of 1.1:1:1.1, so that the blank is placed between the two copper plates to form a preform of a copper plate / blank / copper plate sandwich structure.
[0079] 3.2) Raise the temperature to 400°C within 30 minutes by increasing the pressure by 0.5 MPa for every 100°C increase in temperature. At the same time, increase the working pressure to 4 MPa and keep it at this temperature for 10 minutes.
[0080] 3.3) Raise the temperature to 600°C within 30 minutes by increasing the pressure by 2.5 MPa for every 100°C increase in temperature. At the same time, increase the working pressure to 15 MPa and keep it at this temperature for 10 minutes.
[0081] 3.4) Increase the pressure by 2.5 MPa for every 100°C increase in temperature, raise the temperature to 1020°C within 5 minutes, increase the working pressure to 20 MPa, and keep warm for 10 minutes.
[0082] 3.5) While maintaining the pressure at 20 MPa, raise the temperature to 1250°C within 20 minutes and keep it at this temperature for 10 minutes.
[0083] 3.6) While maintaining the pressure at 20 MPa, the temperature was first lowered to 1000°C within 15 min and kept at 1000°C for 10 min before unloading the pressure and then cooling to room temperature to obtain a multilayer CPC precursor.
[0084] Step 4, post-processing:
[0085] 4.1) Finishing treatment:
[0086] The multilayer CPC precursor obtained in 3.6) is trimmed by machining to make the copper layers on both sides smooth and defect-free with a surface roughness of 0.5 μm. In the trimmed multilayer CPC precursor, the thickness ratio of the copper layer, the molybdenum-copper alloy layer and the copper layer is 1.08:1:1.08.
[0087] 4.2) Rolling treatment:
[0088] Each time rolling, the trimmed multi-layer CPC precursor is first placed in a nitrogen-hydrogen mixed furnace for preheating to 350°C. When the temperature reaches the set stable temperature, it is kept warm for 10 minutes; and the roller is preheated to 100°C; then, the preheated multi-layer CPC precursor and roller are taken out, and the preheated multi-layer CPC precursor is placed in the preheated roller for rolling, and the reduction is guaranteed to be 3%. Repeat several times until the required thickness is reached.
[0089] 4.3) Annealing treatment:
[0090] The material after the rolling treatment in 4.2) is placed in a vacuum annealing furnace, heated to 550° C., and kept warm for 8 hours to obtain the multi-layer CPC composite material.
[0091] Example 3
[0092] This embodiment provides a multi-layer CPC composite material, which is prepared by the following steps:
[0093] Step 1, preparing mixed powder:
[0094] 1.1) Molybdenum powder and copper powder are mixed in a mass ratio of 90:10 to obtain molybdenum-copper powder.
[0095] 1.2) Add ethanol to the molybdenum-copper powder obtained in 1.1), and the amount of ethanol added is 2% of the total mass of the molybdenum-copper powder to obtain an ethanol mixture of molybdenum-copper powder.
[0096] 1.3) The ethanol mixture of molybdenum and copper powders obtained in 1.2) was mixed for 10 hours and then dried at 70° C. for 2 hours to obtain a mixed powder.
[0097] Step 2, compression treatment:
[0098] The mixed powder obtained in 1.3) was placed in a pressing mold, the powder filling height was adjusted to be less than 0.5 of the mold depth, and then placed in an automatic press. The working pressure of the press was selected to be 200 tons, and the holding time was set to 1 second to obtain a density of 8.9 g / cm 3 of the billet.
[0099] Step 3, hot pressing semi-melt infiltration treatment:
[0100] 3.1) The copper plate, the blank and the copper plate are placed in the mold cavity in sequence according to a mass ratio of 1.3:1:1.3, so that the blank is placed between the two copper plates to form a preform of a copper plate / blank / copper plate sandwich structure.
[0101] 3.2) Raise the temperature to 600°C within 40 minutes by increasing the pressure by 1.5 MPa for every 100°C increase in temperature. At the same time, increase the working pressure to 6 MPa and keep it at this temperature for 15 minutes.
[0102] 3.3) Raise the temperature to 900°C within 40 minutes by increasing the pressure by 3.5 MPa for every 100°C increase in temperature. At the same time, increase the working pressure to 20 MPa and keep it at this temperature for 20 minutes.
[0103] 3.4) Raise the temperature to 1080°C within 10 minutes by increasing the pressure by 3.5 MPa for every 100°C increase in temperature. At the same time, increase the working pressure to 30 MPa and keep it at this temperature for 15 minutes.
[0104] 3.5) While maintaining the pressure at 30 MPa, raise the temperature to 1380°C within 30 minutes and keep it at this temperature for 30 minutes.
[0105] 3.6) While maintaining the pressure at 30 MPa, the temperature was first lowered to 1000°C within 20 min and kept at 1000°C for 20 min before unloading the pressure and then cooling to room temperature to obtain a multilayer CPC precursor.
[0106] Step 4, post-processing:
[0107] 4.1) Finishing treatment:
[0108] The multilayer CPC precursor obtained in 3.6) is trimmed by machining to make the copper layers on both sides smooth and defect-free with a surface roughness of 0.5 μm. In the trimmed multilayer CPC precursor, the thickness ratio of the copper layer, the molybdenum-copper alloy layer and the copper layer is 1.28:1:1.28.
[0109] 4.2) Rolling treatment:
[0110] Each time rolling, the trimmed multi-layer CPC precursor is first placed in a nitrogen-hydrogen mixed furnace for preheating to 500°C. When the temperature reaches the set stability, it is kept warm for 30 minutes; and the roller is preheated to 200°C; then, the preheated multi-layer CPC precursor and roller are taken out, and the preheated multi-layer CPC precursor is placed in the preheated roller for rolling, and the reduction is guaranteed to be 8%. Repeat several times until the required thickness is reached.
[0111] 4.3) Annealing treatment:
[0112] Put the material after rolling treatment in 4.2) into a vacuum annealing furnace, heat it to 800℃ and keep it warm for 2h.
[0113] That is, the multi-layer CPC composite material is obtained.
[0114] Experimental Section
[0115] The present invention takes the multi-layer CPC composite materials of Examples 1 to 3 as examples and conducts the following tests thereon.
[0116] 1. Density test
[0117] The present invention tests the mass and volume of the obtained material respectively, and then calculates according to density = mass / volume that the density of the multilayer CPC composite material of Example 1 is ρ = 9.65 g / cm 3 The density of the multi-layer CPC composite materials of Example 2 and Example 3 is close to that of Example 1, which is 97% to 99% of the density of the multi-layer CPC composite material of Example 1.
[0118] 2. Thermal expansion test
[0119] The present invention uses a test instrument of German NETZSCH-DIL 402C, with a measurement range of ±5000 μm, a resolution of 2 nm, and an inert argon atmosphere to test the thermal expansion coefficient of the multilayer CPC composite material prepared in Example 1.
[0120] The test results show that the thermal expansion coefficient of the multilayer CPC composite material of Example 1 is 8.0×10 -6 / K -1 The density of the multi-layer CPC composite materials of Example 2 and Example 3 is close to that of Example 1, which is 95% to 97% of the thermal expansion coefficient of the multi-layer CPC composite material of Example 1.
[0121] 3. Thermal conductivity test
[0122] The present invention uses a test instrument with a device model of LFA467HT, a maximum heating rate of 50K / min, and an inert argon atmosphere to test the thermal conductivity of the multilayer CPC composite material prepared in Example 1.
[0123] The test results show that the thermal conductivity of the multilayer CPC composite material of Example 1 is 212 W / (m×k). The density of the multilayer CPC composite materials of Examples 2 and 3 is close to that of Example 1, which is 96% to 98% of the thermal conductivity of the multilayer CPC composite material of Example 1.
[0124] 4. Tensile strength test
[0125] The present invention adopts a test instrument with the equipment model of UTM-5105, the parallel section size of the plate is greater than 25 mm, and the thickness is greater than 2 mm. The test standard conforms to GB / T228.1-2021.
[0126] The test results show that the tensile strength of the multi-layer CPC composite materials of Examples 1 to 3 is within the range of 600 MPa to 750 MPa.
[0127] In summary, the multilayer CPC composite material obtained by the preparation method of the present invention has a large density, excellent thermal expansion coefficient and thermal conductivity, and excellent tensile strength, which shows that the preparation method of the present invention can indeed improve the bonding strength between the plates on the basis of reducing the process of the preparation process, thereby effectively improving the comprehensive performance of the overall material.
[0128] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a multilayer CPC composite material, characterized in that: The following steps are involved: Molybdenum powder, copper powder and a mixing aid are mixed and then dried to obtain a mixed powder; The mixed powder is pressed to obtain a blank; Subsequently, the blank is placed between two copper plates to form a preform having a copper plate / blanket / copper plate sandwich structure; The preform is subjected to a hot pressing semi-melt infiltration treatment to achieve a preliminary composite of the molybdenum-copper alloy layer and the copper plates on both sides to obtain a multilayer CPC precursor; After the multi-layer CPC precursor is flattened, rolling and annealing are performed in sequence to obtain the multi-layer CPC composite material.
2. The preparation method according to claim 1, characterized in that The hot pressing semi-infiltration treatment is carried out by the following steps: the temperature is raised to 400°C to 600°C and the working pressure is increased to 4MPa to 6MPa by increasing the pressure by 0.5MPa to 1.5MPa for every 100°C increase in temperature, and then the first stage of heat preservation treatment is carried out; The second stage of heat preservation treatment is carried out by increasing the pressure by 2.5MPa to 3.5MPa for every 100℃ increase in temperature, raising the temperature to 600℃ to 900℃ and increasing the working pressure to 15MPa to 20MPa; The third stage of heat preservation treatment is carried out by increasing the pressure by 2.5MPa to 3.5MPa for every 100℃ increase in temperature, raising the temperature to 1020℃ to 1080℃ and increasing the working pressure to 20MPa to 30MPa; Under the condition of maintaining the pressure at 20MPa to 30MPa, the temperature is raised to 1250℃ to 1380℃, and the fourth stage of heat preservation treatment is carried out; Under the condition of maintaining the pressure at 20MPa-30MPa, the temperature is lowered to <1000°C, the pressure is unloaded, and then the mixture is cooled to room temperature to obtain a multilayer CPC precursor.
3. The preparation method according to claim 2, characterized in that: The first stage of heat preservation treatment lasts for 10 to 15 minutes; The second stage of heat preservation treatment lasts for 10 to 20 minutes; The third stage of heat preservation treatment lasts for 10 to 15 minutes; The fourth stage of heat preservation treatment lasts for 10 to 30 minutes.
4. The preparation method according to claim 1, characterized in that: The particle size of the molybdenum powder is 20 μm to 400 μm; the particle size of the copper powder is 30 μm to 500 μm; The mass ratio of the molybdenum powder to the copper powder is 80-90:10-20.
5. The preparation method according to claim 1, characterized in that: The mixing aid is ethanol; The mass of the mixing auxiliary agent is 0.5% to 2% of the total mass of the molybdenum powder and the copper powder.
6. The preparation method according to claim 1, characterized in that: In the sandwich structure of the preform, the mass ratio of the copper plate, the blank and the copper plate is 1.1-1.3:1:1.1-1.
3.
7. The preparation method according to claim 1, characterized in that: During the pressing process, the density of the blank is controlled at 7.8 g / cm 3 ~8.9g / cm 3 .
8. The preparation method according to claim 1, characterized in that: The rolling process is performed by rolling for multiple times to a desired thickness; and the reduction amount of each rolling is 3% to 8%.
9. The preparation method according to claim 1, characterized in that: The annealing treatment temperature is 550° C. to 800° C., and the annealing holding time is 2 h to 8 h.
10. A multi-layer CPC composite material prepared by the preparation method according to any one of claims 1 to 9.